[S.S. Rita Garcia]
028-0127-001 Consulado General de España en la Gran Bretaña J.L. Resines, representative of the Director de Marina, Santander. 21 Cavendish Square, W.1. (Tel: Langham 2603) The only vessels that will be running between the Bristol Channel and Santander in the near future will be: S.S. "Rio Liera" which will arrive Port Talbot on the 22nd. inst; sailing Port-Talbot - Santander 30th December The Consignees of this vessel in Cardiff will be: Messrs. Emlyn Jones Griffin & Co. Ltd., 4 Dock Chambers, Cardiff, S.S."Rita Garcia" 7000 tons deadweight, which will arrive at Glasgow on the 26th. inst., thence from the Clyde in ballast for Cardiff on January 2nd., so that she will be ready to leave Cardiff for Santander January 6th. The agents for this vessel will be as for the above. The merchandise that may be shipped by these vessels will be consigned either to the Civil Governor of the Province of Santander, or to the director de Marina of the same province. 292/946/28/127